Pengaruh Celebrity Endorser Suhay Salim terhadap Minat Beli Produk Pixy (Survey Pada Remaja Akhir di Jakarta Pusat) - Marshella Tsalatsa Syafira; Salman (UNIVERSITAS KALBIS, 2022)
The development from conventional media to new media has made many companies take advantage of new media to carry out marketing activities so that activities run faster, more efficiently, and reach a wider target without any time or space limits. This research has a purpose to know how big is the influence of celebrity endorser, Suhay Salim, towards customer’s buying interest for Pixy products among teenagers in Central Jakarta. This research is using positivistic paradigm with a quantitative approach and explanative survey method. This investigation employs the Stimulus-Response (S-R) hypothesis. For this study, a questionnaire is utilized to gather data, which is then analyzed using validity tests, reliability tests, Pearson's Product Moment correlation analysts, normality tests, hypothesis tests, coefficients of determination, and basic linear regression analyses. Based on the outcome of the hypothesis test, it can be concluded that Suhay Salim's celebrity endorsement influences the purchasing interest of adolescents in Central Jakarta for Pixy products.